Exergoeconomic assessment of the ejector-based battery thermal management system for electric and hybrid-electric vehicles. (15th April 2022) - Alkhulaifi, Yousif M.; Qasem, Naef A.A.; Zubair, Syed M.
Abstract: The battery is a critical component for operating electric and hybrid electric vehicles where temperature control is vital for safe and efficient operation. In this paper, the ejector-based battery thermal management system (BTMS) performance is compared to the basic BTMS from thermal and exergoeconomic perspectives. The ejector is added to mix the refrigerant streams from the cabin evaporator and battery chiller, thus delivering the mixture to the compressor with higher pressure to reduce compression power and improve system performance. The exergoeconomic study is carried out for different evaporator, chiller, and condenser temperatures and different battery thermal loads to illustrate the ejector-based system's technical and economic feasibility. Results show an optimal (minimal) total system cost rate of 0.9092 US$/h for the ejector-based system, compared to 1.0222 US$/h for the basic system (11.1% reduction). Based on the applied conditions, the total exergy destruction is found to be 1.596 kW for the ejector-based BTMS and 2.243 kW for the basic BTMS, representing a 28.8% reduction compared to the basic system. Highlights: Exergo-economic studies are carried out for the ejector-based thermal management system. The new system significantly improves over the original refrigerant-coolant system. A cost rate reduction of 11% is achieved in the new system compared to the original design. An exergy destruction reduction of 28.8% is achieved in the new (proposed) system. A Second Law efficiency improvement of 39% is achieved in the new system.